?f -LACUNARY STATISTICAL CONVERGENCE OF ORDER ? - Kasap, Mithat; Altinok, Hifsi (Univ Nis, 2024)
The main object of this article is to introduce the concepts of Of-lacunary statistical convergence of order 3 and strong Of-lacunary summability of order 3 for sequences of fuzzy numbers and define some sequence classes related to these concepts. We give some inclusion relations between those sequence classes.
Keywords: strong Delta(f)-lacunary summability; Delta(f)( )-lacunary statistical convergence